Emotion recognition using brian signals based on time-frequency analysis and supervised learning algorithm - Hossain, Prommy Sultana Ferdawoos; Shaikat, Istiaque Mannafee; George, Fabian Parsia (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.